Tracing back to the source: Understanding the corporate governance of boards of directors in Chinese SOEs - Zhengfei Lu; Jigao Zhu (China Journal of Accounting Research, 2020)
Based on the relevant theories of corporate governance and the special institutional background of Chinese state-owned enterprises (SOEs), this paper systematically reviews the literature on the independence and governance effect of SOE boards. We find that the governance effect of SOE boards is driven by the dual characteristics of SOEs: state involvement in ownership and market incentives. With the state involved in ownership, SOEs adhere to the leadership of the Communist Party of China (CPC), which results in an enhanced governance effect. Under market incentives, SOEs tend to have an optimal board structure that helps mitigate both the shareholder-management agency problem (Type I agency problem) and the controlling shareholder-minority shareholder agency problem (Type II agency problem). In terms of the governance effect of boards, directors appointed by non-controlling shareholders are effective in alleviating Type I and Type II agency problems, and this highlights the importance of mixed-ownership reforms in SOEs. Independent directors, especially those with a professional background, also play a role in improving corporate governance. However, independent directors in SOEs have relatively weak incentives to monitor, which limits their governance effect. This paper shows positive implications for promoting mixed-ownership reforms and improving board governance in SOEs.
Keywords: 650; Board of directors; Governance effect; Independence; SOEs